Artificial Salmonella vaccines: Salmonella typhimurium O-antigen-specific oligosaccharide-protein conjugates elicit opsonizing antibodies that enhance phagocytosis. - Jörbeck, H J (1981)
Outbred NMRI mice and rabbits were vaccinated with different artificial Salmonella typhimurium immunogens and the specificity and activity of elicited antibodies were studied in in vivo and in vitro phagocytosis assays. The Salmonella immunogens used were: (i) the synthetic disaccharide, abequose (formula see text) D-mannose, representative of Salmonella O antigen 4, covalently linked to bovine serum albumin (BSA); (ii) the octa- and dodecasaccharides, (formula see text) covalently linked to BSA; and (iii) whole heat-killed Salmonella. Rabbit antibodies passively administered to mice significantly enhanced the clearance of intravenously injected S. typhimurium challenge bacteria from the bloodstream. The clearance rate and the titer of anti-O-antigen-specific antibodies correlated. The clearance rate of an S. thompson (O6,7) strain, which has a different O antigen, was the same irrespective of the rabbit serum given. NMRI mice actively immunized with the various oligosaccharide-BSA conjugates had a significantly increased clearance rate of S. typhimurium only. In the in vitro assay, mouse antioligosaccharide-BSA sera promoted phagocytosis of S. typhimurium, but not S. thompson, when incubated with complement and mouse peritoneal exudate cells activated with Freund complete adjuvant.